(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The basic of achievement so achievement motive i.e., motive to achieveThe present study assumes greater significance in case of high school students as they are at their adolescent period. The majority of psychologists are agreed on that it is a time of stress and strain. So we must give individual attention to hired need achievement which is greatly affected by variab1es like achievement motivation and intelligent. So there is dine need to explore the relationship of educational world and finding can reveal worthy facts and enrich our intellectual horizons.